Smoking Cessation, Weight Gain, Cardiovascular Risk, and All-Cause Mortality: A Meta-analysis. Issue 12 (20th April 2021) - Wang, Xiaowen; Qin, Li-Qiang; Arafa, Ahmed; Eshak, Ehab S; Hu, Yonghua; Dong, Jia-Yi
Abstract: Introduction: Quitting smoking usually results in weight gain, rising the concern that weight gain after smoking cessation may attenuate the benefits of smoking quitting on cardiovascular health. Aims and Methods: We aimed to examine the risk of cardiovascular disease (CVD) among smoking quitters compared with smokers, stratified by post-cessation weight change. We searched PubMed, Scopus, and Web of Science for eligible studies published before September 2020. Cohort studies examining the relative risk of CVD among smoking quitters stratified by post-cessation weight change, with smokers being treated as the reference, were included. Two investigators extracted the key characteristics of each included study using a standard electronic form. Results: We identified nine studies for this meta-analysis. Compared with smokers, the pooled RRs (95% confidence interval) of CVD among quitters with weight gain and among those without were 0.74 [0.66, 0.83] and 0.86 [0.80, 0.92], with no evidence of heterogeneity between studies being observed. Moreover, the associations appeared to be significantly stronger among quitters with weight gain than those without, particularly in the analysis of coronary heart disease (CHD) and stroke (pooled RRs = 0.65 [0.59, 0.71] vs. 0.79 [0.71, 0.88] for CHD and 0.67 [0.62, 0.73] vs. 0.76 [0.72, 0.81] for stroke, respectively; p for interaction <.05). Conclusions: Smoking cessation was associated with a significantly lower risk of CVD and all-cause mortality, regardless of post-cessation weight gain. A greater risk reduction among quitters with weight gain than those without merits further investigations. Implications: Quitting smoking usually results in weight gain and increases the risk of type 2 diabetes. We found that the risk reduction in CVD and all-cause mortality associated with smoking cessation was greater in quitters with weight gain than that in quitters without, especially in CHD and stroke. Despite weight gain and increased risk of type 2 diabetes, quitting smoking remains effective in the prevention of CVD.